Effect of HIV-1 Integrase Resistance Mutations When Introduced into SIVmac239 on Susceptibility to Integrase Strand Transfer Inhibitors - Hassounah, Said A. (American Society for Microbiology, 2014)
Studies on the in vitro susceptibility of SIV to integrase strand transfer inhibitors (INSTIs) have been rare. In order to determine the susceptibility of SIVmac239 to INSTIs and characterize the genetic pathways that might lead to drug resistance, we inserted various integrase (IN) mutations that had been selected with HIV under drug pressure with raltegravir (RAL), elvitegravir (EVG), and dolutegravir (DTG) into the IN gene of SIV. We evaluated the effects of these mutations on SIV susceptibility to INSTIs and on viral infectivity. Sequence alignments of SIVmac239 IN with various HIV-1 isolates showed a high degree of homology and conservation of each of the catalytic triad and the key residues involved in drug resistance. Each of the G118R, Y143R, Q148R, R263K, and G140S/Q148R mutations, when introduced into SIV, impaired infectiousness and replication fitness compared to wild-type virus. Using TZM-bl cells, we demonstrated that the Q148R and N155H mutational pathways conferred resistance to EVG (36- and 62-fold, respectively), whereas R263K also displayed moderate resistance to EVG (12-fold). In contrast, Y143R, Q148R, and N155H all yielded low levels of resistance to RAL. The combination of G140S/Q148R conferred high-level resistance to both RAL and EVG (>300- and 286-fold, respectively). DTG remained fully effective against all site-directed mutants except G118R and R263K. Thus, HIV INSTI mutations, when inserted into SIV, resulted in a similar phenotype. These findings suggest that SIV and HIV may share similar resistance pathways profiles and that SIVmac239 could be a useful nonhuman primate model for studies of HIV resistance to INSTIs. IMPORTANCE The goal of our project was to establish whether drug resistance against integrase inhibitors in SIV are likely to be the same as those responsible for drug resistance in HIV. Our data answer this question in the affirmative and show that SIV can probably serve as a good animal model for studies of INSTIs and as an early indicator for possible emergent mutations that may cause treatment failure. An SIV-primate model remains an invaluable tool for investigating questions related to the potential role of INSTIs in HIV therapy, transmission, and pathogenesis, and the present study will facilitate each of the above.